The Effect of Mung Bean Extract on The Increase of Hemoglobin Levels in Pregnant Women in Trimesters II and III - Ratnaningsih, Tri Astuti; Mariza, Ana; Suharman, Suharman; Evrianasari, Nita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Anemia is a common blood disorder that occurs when the level of red blood cells in the body becomes too low. The incidence of anemia in pregnant women at Bandar Negeri Suoh Primary Health Care in 2020 was 72 cases; it was 85 cases in 2021; and it was 87 cases in 2022. One way to help increase hemoglobin levels in pregnant women is by consuming mung bean extract. Mung bean extract contains iron, which can help with oxygen circulation and increase hemoglobin levels. To determine the effect of mung bean extract on the increase of hemoglobin levels in pregnant women in trimesters II and III in the working area of Bandar Negeri Suoh Community Primary Health Care in 2023. This research was a quantitative study using a pre-experimental design and a one-group pretest and posttest design. The population of this study consisted of pregnant women in trimesters II and III with anemia in the working area of Bandar Negeri Suoh Community Primary Health Care. The total was 38 people, with 30 people as the sample. The sampling technique used in this study was purposive sampling, and the data analysis involved the Wilcoxon test. The average hemoglobin level before consuming mung bean extract was 10.243 g/dL, and after consuming mung bean extract, it increased to 11.37 g/dL. The Wilcoxon test result yielded a p-value of 0.000 < 0.05, indicating that there was an effect of mung bean extract on the increase of hemoglobin levels in pregnant women in trimesters II and III in the working area of Bandar Negeri Suoh Primary Health Care in 2023. There was an effect of mung bean extract on the increase of hemoglobin levels in pregnant women in trimesters II and III in the working area of Bandar Negeri Suoh Primary Health Care in 2023. Keywords: Hemoglobin Level, Mung Bean Extract, Pregnant Women